Small-molecule probe reveals a kinase cascade that links stress signaling to TCF/LEF and Wnt responsiveness. Issue 5 (20th May 2021) - Cheng, Jiongjia; Tsuda, Masanao; Okolotowicz, Karl; Dwyer, Mary; Bushway, Paul J.; Colas, Alexandre R.; Lancman, Joseph J.; Schade, Dennis; Perea-Gil, Isaac; Bruyneel, Arne A.N.; Lee, Jaechol; Vadgama, Nirmal; et al.
Summary: Wnt signaling plays a central role in tissue maintenance and cancer. Wnt activates downstream genes through β-catenin, which interacts with TCF/LEF transcription factors. A major question is how this signaling is coordinated relative to tissue organization and renewal. We used a recently described class of small molecules that binds tubulin to reveal a molecular cascade linking stress signaling through ATM, HIPK2, and p53 to the regulation of TCF/LEF transcriptional activity. These data suggest a mechanism by which mitotic and genotoxic stress can indirectly modulate Wnt responsiveness to exert coherent control over cell shape and renewal. These findings have implications for understanding tissue morphogenesis and small-molecule anticancer therapeutics. Graphical abstract: Highlights: PAWI-1, 2 are small molecules with dual p 53 a gonist and W nt i nhibitor activities PAWIs bind tubulin and activate stress signaling Stress signaling through ATM, AURK, and HIPK inhibits TCF/LEF transcriptional activity PAWIs inhibit the ability of a cell to respond to Wnt Abstract : Cheng et al. used high-throughput screening to identify a small molecule with dual p53 agonist and Wnt inhibitory activity. Named PAWI, the compounds were used to trace a kinase cascade linking stress signaling to the regulation of TCF/LEF function and the control of Wnt-dependent gene expression.